How do nuclear isomers influence the gamma-ray bursts in binary neutron star mergers? - Hamilton, Maria C. Babiuc; Powell, Joseph I. (Frontiers in Astronomy and Space Sciences, 2024)
Neutron star mergers are astrophysical “gold mines,” synthesizing over half of the elements heavier than iron through rapid neutron capture nucleosynthesis. The observation of the binary neutron star merger GW170817, detected both in gravitational waves and electromagnetic radiation, marked a breakthrough. One electromagnetic component of this event, the gamma ray burst GRB 170817A, has an unresolved aspect: the characteristics of its prompt gamma-ray emission spectrum. In this work, we investigate that gamma-ray spectra in such GRBs may be influenced by de-excitations from isomeric transitions. Our study begins with a review of current knowledge on GRB structure and of r-process nucleosynthesis in neutron star collisions, focusing on the role of nuclear isomers in these settings. We then test our hypothesis by developing criteria to select representative isomers, based on known solar element abundances, for modeling GRB spectral characteristics. We integrate these criteria into an interactive web page, facilitating the construction and analysis of relevant gamma-ray spectra from isomeric transitions. Our analysis reveals that three isomers—90Zr, 207Pb, and 89Y—stand out for their potential to impact the prompt GRB spectrum due to their specific properties. This information allows us to incorporate nuclear isomer data into astrophysical simulations and calculate isomeric abundances generated by astrophysical r-processes in neutron star mergers and their imprint on the detected signal.